2014
DOI: 10.1158/1535-7163.mct-14-0151
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Time-Dependent Effects of Irradiation on Multidrug Resistance in a Non–Small Lung Cancer Cell Line

Abstract: Multidrug resistance (MDR) in cancer is known to decrease the therapeutic efficacy of chemotherapy. The effects of irradiation on MDR in cancer cells remain unclear. Tc-99m methoxyisobutylisonitrile (MIBI) exhibits the same ATP-binding cassette (ABC) transporter kinetics as the chemotherapeutic compound doxorubicin. In this study, we investigated the synergistic effects of chemotherapeutics and irradiation [0 Gy: C (control) group; 3, 6, 9, 12 Gy: I (irradiation) group] in the human non-small lung cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A modified protocol as previously described was used for iodide accumulation studies [ 34 ]. Briefly, K1, FTC-133, or K1-NIS cells treated with vehicle (0.1% DMSO in media) or 3 and 20 μM lenvatinib mesilate (lenvatinib; supplied from Eisai Co., Ltd., Tokyo, Japan) for 48 h were harvested using Accutase (Innovative Cell Technologies, Inc., California, USA, AT-104) and suspended in 7.0 mL of complete medium at a concentration of 1–2 × 10 6 cells/mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified protocol as previously described was used for iodide accumulation studies [ 34 ]. Briefly, K1, FTC-133, or K1-NIS cells treated with vehicle (0.1% DMSO in media) or 3 and 20 μM lenvatinib mesilate (lenvatinib; supplied from Eisai Co., Ltd., Tokyo, Japan) for 48 h were harvested using Accutase (Innovative Cell Technologies, Inc., California, USA, AT-104) and suspended in 7.0 mL of complete medium at a concentration of 1–2 × 10 6 cells/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The intracellular accumulation ratio (CPMin/CPMout) was calculated as the ratio of radioactivity concentration inside the cell to that found in the supernatant. The accumulation ratio equation was calculated as follows using the radioactivity measurements in cell pellets and a standard representing the supernatant concentration together with an independent cell volume measurement [ 34 ]: where counts per minute pellet is the measured radioactivity rate of the pellet, counts per minute supernatant is the measured radioactivity rate of the supernatant, volume pellet = volume supernatant = 300 μL, and #cells pellet = volume pellet × density pellet = 300 μL × (3.1, 2.8, or 3.3 × 10 5 cells/μL)*, where * is the constant density per 1 μL of packed K1, FTC-133, or K1-NIS cells, respectively. The constant density of packed cells was measured using a Packed Cell Volume Tube (Techno Plastic Products AG, Trasadingen, Switzerland, 87005).…”
Section: Methodsmentioning
confidence: 99%
“…Therapies capable of interfering with the harmful action of the MDR1 gene, which produces a protein capable of blocking the entry of the chemotherapy drug into the cell (thus protecting it from its action) are being studied. Other genes overexpressed in MDR tumors are those that code for ATP-binding cassette (ABC) transporters, such as P-glycoprotein (Pgp), multiple-resistance-associated protein 1 (MRP1) and others, in the plasma membrane [ 174 , 175 ]. The overexpression of these ABC transporters causes the energy-dependent escape of chemotherapeutic agents from the intracellular volume to the extracellular environment.…”
Section: Validation Of Radiopharmaceuticals In Vitro By γ-Countermentioning
confidence: 99%
“…Several clinical studies have shown that MIBI is a valid predictor of chemotherapy response in non-small cell lung cancer [ 181 , 182 , 183 , 184 ]. Yumiko et al [ 175 ] used [ 99m Tc]MIBI in vitro and doxorubicin in vivo to investigate how to optimally combine chemotherapy and radiotherapy to achieve the maximum synergistic effect in chemoradiotherapy, using non-small tumor cells and irradiation. To evaluate MDR suppression after γ-ray irradiation, [ 99m Tc]MIBI accumulation was performed in an in vitro study in human NSCLC cells.…”
Section: Validation Of Radiopharmaceuticals In Vitro By γ-Countermentioning
confidence: 99%